2019
DOI: 10.1038/s41598-018-37836-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of spotted fever group rickettsiae and their association with host ticks in Japan

Abstract: Spotted fever group (SFG) rickettsiae are obligate intracellular Gram-negative bacteria mainly associated with ticks. In Japan, several hundred cases of Japanese spotted fever, caused by Rickettsia japonica, are reported annually. Other Rickettsia species are also known to exist in ixodid ticks; however, their phylogenetic position and pathogenic potential are poorly understood. We conducted a nationwide cross-sectional survey on questing ticks to understand the overall diversity of SFG rickettsiae in Japan. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 48 publications
(52 reference statements)
0
24
1
1
Order By: Relevance
“…Unlike most SFGR, infections with R. tamurae are not associated with high fever, generalized rash, lymphadenopathy as it is often seen in other spotted fever rickettsioses. R.tamurae was first isolated from A. testudinarium ticks in Japan and has the wild boar and domestic pigs as it primary host although it can also infest deer, cattle, other ungulates and domestic livestock as well as humans [47][48][49]. R. tamurae has been isolated from the skin biopsy specimen from wild boars and also in ticks [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most SFGR, infections with R. tamurae are not associated with high fever, generalized rash, lymphadenopathy as it is often seen in other spotted fever rickettsioses. R.tamurae was first isolated from A. testudinarium ticks in Japan and has the wild boar and domestic pigs as it primary host although it can also infest deer, cattle, other ungulates and domestic livestock as well as humans [47][48][49]. R. tamurae has been isolated from the skin biopsy specimen from wild boars and also in ticks [47].…”
Section: Discussionmentioning
confidence: 99%
“…R. tamurae infection according to Imaokaa et al [ 47 ] is associated with symptoms such as mild local inflammatory signs like swellings, erythema, redness heat and pain. Symptoms of R. tamurae infection mimics cellulitis with increased serum titers of antibody against the organism [ 48 ]. Unlike most SFGR, infections with R. tamurae are not associated with high fever, generalized rash, lymphadenopathy as it is often seen in other spotted fever rickettsioses.…”
Section: Discussionmentioning
confidence: 99%
“…tamurae, R. monacensis, and R. asiatica , and several other uncharacterized rickettsial species/genotypes have been detected (4, 5). R. asiatica is the only named species of these whose genome sequence is not available.…”
Section: Announcementmentioning
confidence: 99%
“…R. asiatica , initially described as a Rickettsia strain IO-1 T , was first isolated from Ixodes ovatus ticks collected in Fukushima Prefecture, Japan, in 1993 (6, 7). A recent study revealed that R. asiatica had a strong host specificity, where it was detected only in I. ovatus (5).…”
Section: Announcementmentioning
confidence: 99%
“…R. conorii, są kleszcze należące do jednego gatunku, podczas gdy innych (np. R. rickettsii) są kleszcze należące do kilku rodzajów [9].…”
Section: Rezerwuar Oraz Wektorunclassified